Economic Globalization and Third World Countries: Assessing the Impact and Prospects in Nigeria - Davies, Emmanuel Opuene; Emesibe, Vincent Obiora (NIU Journal of Social Sciences; Vol 5 No 3 (2019): KIU Journal of Social Sciences, Vol. 5 No. 3, September 2019, 2019)
Contemporary international relation is characterized by intensive integration of national economies into the global economy dominated by advanced capitalist countries such as members of the G8. This gives rise to unbridled competition for national and international resources, and raises the question of whether economic globalization fosters interdependence or exploitation and dependency. Thus, this paper examines economic globalization and probes the structures that propel and sustain the globalization process. The paper also analyses the impact and prospects of economic globalization for the third world with special focus on Nigeria. Sources of data for this study include textbooks, journals, library research, internet and works of other scholars related to this study. The paper employs dependency framework of analysis and argues from the radical perspective that views globalization as capitalist and imperialist expansion thus, economic globalization is the substructure, premise and motive force of the all-encompassing process called globalization. Basically the contemporary economic globalization is manifest in economic reform programmes contained in the liberalization policies and free market economy. The work concludes that given the exploitative impact, and the dependent and disadvantaged positions of Nigeria and other third world countries in the contemporary economic globalization process, Nigeria and other third world countries’ socio-economic and political future seem bleak. However, the paper recommends that, economically, the liberalization policies (embodied in SAP) should be rolled back and the economy diversified rapidly with emphasis on manufacturing industry and agricultural sector. Internationally, Nigeria and the rest of the third world countries should integrate to gain greater say in the dominant economic structures/institutions such as Bretton Wood institutions, World Trade Organization etc. which propel and sustain economic globalization. Keywords : Globalization, Third World, Economic, Capitalism, Imperialism, International Relations, impact, Nigeria.